KARAKTERISTIK KOMPON KARET DENGAN BAHAN PENGISI ARANG AKTIF TEMPURUNG KELAPA DAN NANO SILIKA SEKAM PADI - Popy Marlina, Filli Pratama, Basuni Hamzah, Rindit Pambayun TIN (Jurnal Teknologi Industri Pertanian, 2015)
The objective of the research was to the characterize rubber compound added with the fillers of activated coconut shell carbon and nano silica from rice husks. The experiment was done based on factorial completely randomized design with two factors as treatments with three replications. The first factor was the concentration of activated coconut shell carbon (0, 10, 20, 30, 40 and 50 phr), and the second factor was nano-sized (350 to 400 nm in diameter) silica from rice husks (50, 40, 30, 20, 10 and 0 phr). The parameters measured included the hardness, tensile strength, elongation at break, and abrasion resistance. The results showed that the addition of activated coconut shell carbon and nano-sized silica from rice husks, as well as the interactions had highly significant effect on all parameters. The hardness of rubber compounds ranged from 24 to 58 Shores A, the tensile strength were15 to 71 N/m2, the elongation at breakswere108 to 689%, and the abrasion resistances ranged 427 to 1002 cm3. The addition of activated coconut shell carbon and nano-sized silica from rice husk increased the hardness, decreased the tensile strength, elongation at break and abrasion resistance of the rubber compound. The treatment of A2S2 (10phr of activated coconut shell carbon and 40 phr of nano-sized silica from rice husk), A4S6 (30phr of activated coconut shell carbon and 0 phr of nano-sized silica from rice husk) and A5S5 (40phr of activated coconut shell carbon and 10 phr of nano-sized silica from rice husk), met the requirements of the Indonesian National Standards for pads dock rubber compound (SNI 06-3568-2006).Keywords: coconut shell, rice husk, rubber compound, silica